Pengaruh Atraksi Wisata Alam dan Motivasi Wisatawan terhadap Keputusan Berkunjung Wisatawan ke Kawasan Wisata Ciwidey dan Pangalengan - Dadan Ramdani (Jurnal Wacana Ekonomi, 2018)
The tourist area of Ciwidey and Pangalengan is part of South Bandung region and making the main purpose of visiting tourists, every year the number of tourist visits to Pangalengan and Ciwidey experienced instability. The decision to visit, the main problem is examined in the study and purpose of this researxh is to know the extent of the influence natural attractions and tourist motivation against the decision of visit in this study. Natural attractions witch consists of a state nature, human resources, means of accommodation and infrastructure. Motivation tourists with a driving factor consists of recreational, diversionary, experimental, experiental and existential. Variabel decision of visit which consists of the selection activity, travel benefits, travel options, destination and time of the visit. The type of research use descriptive quantitative approach with verifikatif, the method used a systematic sampling technique with survey and using multiple regression analysis test. The sample in this study at least equal as 100 respondents. The research results showed the natural attractions with the dimension of highest rated infrastructure and the lowest dimensional and assesment of the state nature. Motivation tourists with dimensions existensial get highest value, and the lowest assessment is experiental and recreational. While the decison variables of a visit by a factor of election activity tour get the highest scoring and lowest scoring that is the slection of travel benefits. Research results showed the existence of very positive influence among the natural attractions and tourist motivation against the decision of a visit.